METHYL PARATHION IMPACT ON THE ESTERASES OF A FRESHWATER TELEOST TILAPIA MOSSAMBICA (PETERS) - Rao, K Siva Prasada; Rao, K R S Sambasiva; Prasad, K Sathya; Rao, K V Ramana (Indian Journal of Fisheries, 2011)
Acetylcholinesterase activity decreased in muscle, gill, liver and brain tissuesof T. mossambica with a corresponding increase in acetylcholine content followingmethyl parathion exposure, suggesting a disruption in the nerve impulse conduction.The electrophoretic study of esterases in the various tissues of Tilapia mossambicasuggests that there are about six anodally migrating bands and there is aninhibition of esterase bands in muscle, gill, liver and brain tissues during subacutemethyl parathion impact and it is found to be tissue specific